DYNAMIC SYNTHESIS AND RESEARCH OF LINEAR TWO-DIMENSIONAL SYSTEM OF REGULATION OF THE TGVD D-27 SCREW FANS - Єнчев, С.; Павелко, О. (Science-based technologies, 2012)
The synthesis of two-dimensional linear control systems hvyntoventylyatoramy (GW), whose purpose - to maintain with the necessary quality of given values of of frequency of rotation the front and rear propeller fans.